Does the Process of Counseling Minors Require Parental Consent: Requirement or Necessity? - Novianti Novianti (International Journal of Counseling and Psychotherapy, 2024)
Background: The requirement of parental consent in counseling minors is a controversial topic, with varying views on whether it is a necessity or simply a procedural formality. This study seeks to explore the urgency and implications of parental consent in the counseling process for minors. Objective: The objective of this study is to review the significance of parental consent in counseling minors, particularly focusing on whether it should be considered a requirement or a mere condition for counseling. This research was conducted in 2024. Method: This study employs a systematic literature review (SLR) approach, synthesizing and analyzing data from journal articles and books retrieved from academic databases such as Google Scholar, PubMed, Harzing, and Mendeley. Results: The findings suggest that parental consent functions as a condition rather than a strict requirement. While it determines whether counseling can take place, it does not significantly affect the actual implementation or outcomes of the counseling process. Conclusion: Counselors should prioritize the rights and beliefs of minors in the counseling process. Further research is needed to understand the extent to which minors can make decisions without parental consent. Contribution: This research provides valuable insights for counselors, offering a practical guide for navigating the ethical challenges surrounding parental consent in counseling minors.